The Jihad of Economic: The Spirit of Islamic Economic Movement by Kyai in Madura - Zainal Abidin (Universitas Islam Negeri Ar-Raniry, 2015)
The dynamics that occur in the business by kyai in Pamekasan is dynamic in the wholeside of the boarding school like the actors, software, and hardware of a boarding school, where the kyaias a determinant factor of the dynamics including the dynamics of business. Kyai and the boardingschool do the business can be differentiated into three types, namely: kyai of business, a boarding schoolof business, and kyai and boarding school of business. It was implemented in a manner that istiqamah,consistent, resignation and exert all the ability to get kosher profits according to shariah. The spiritualvalue of business by kyai is the crystallization of ‘aqidah, shariah, and akhlaq which is based on Al-Quranand Al-Sunnah, which includes economic jihad, 'iffah and businesses as a movement of da’wah namelyda’wah bi al- hal as a basic. Kyai who do the business is able to meet all levels of the hierarchy of needsranging from physiological needs to self-actualization needs of kyai as a personal of himself as well asleaders of boarding schools, so kyai be independent to do everything according to Kyai’s idealism withoutintervention from the other. ABSTRAK - Dinamika yang yang terjadi dalam bidang bisnis oleh kyai di Pamekasan adalah dinamikadi seluruh sisi pesantren yang seperti para pelaku, perangkat lunak dan perangkat keras sebuahpesantren, dimana kyai sebagai faktor penentu dinamika termasuk dinamika bisnis. Kyai dan pesantrenmelakukan bisnis yang dapat dibagi menjadi tiga tipe, yaitu: bisnis kyai, bisnis pesantren, dan kyai danpesantren bisnis. Hal ini diimplementasikan secara istiqamah, konsisten, dikenal dan digunakan padaseluruh kemampun untuk mendapatkan keuntungan yang layak sesuai dengan syari’ah. Nilai spiritualdalam bisnis oleh kyai adalah kristaliasi dari ‘aqidah, syari’ah dan akhlak yang berdasarkan Al Qur’andan Al Sunnah, termasuk ekonomi jihad, ‘iffah dan bisnis sebagai suatu gerakan dakwah yang disebutdengan da’wah bi al- hal sebagai dasarnya. Kyai yang melakukan bisnis mampu berhadapan dengansemua tingkatan hierarki kebutuhan dimulai dari kebutuhan psikologis, hingga kebutuhan aktualisasidiri kyai sebagai pribadi dan juga sebagai pemimpin pesantren, maka kyai dapat bebas melakukansegala sesuatu menurut idealism kyai tanpa adanya intervensi dari pihak lain.